PENDAMPINGAN BACA KITAB KUNING DENGAN MEDIA KITAB AMSILATUT TASRIFIYYAH DI MUSHOLLA WALISONGO SEMBORO JEMBER - Nafsah, Nor Holis bin; Muhtarulloh, Muhammad (An-Nuqthah, 2025)
The use of learning media, especially in Arabic language learning, has the potential to improve students' language skills. This research aims to determine the results of learning the yellow book with the amsilatut tasrifiyah book media for students at the Walisongo Semboro Jember Musholla. By implementing this learning media, it is hoped that it can make students easier to understand the basic rules in Arabic. This study uses a qualitative method. And this research concludes that learning with the amsilatut tasrifiyah book media can have a positive impact on improving the ability to read the yellow book for students at the Walisongo Semboro Jember Musholla. This is evidenced by the fact that all the assisted objects got a score above 75 which is considered good, there is even one student who got the best score with a score of 80.